Effectiveness of community-based football compared to usual care in men with prostate cancer: Protocol for a randomised, controlled, parallel group, multicenter superiority trial (The FC Prostate Community Trial). Issue 1 (December 2016) - Bjerre, Eik; Bruun, Ditte; Tolver, Anders; Brasso, Klaus; Krustrup, Peter; Johansen, Christoffer; Christensen, Robin; Rørth, Mikael; Midtgaard, Julie
Abstract Background Prostate cancer is the most common non-cutaneous malignancy in men. Today most patients may expect to live years following the diagnosis and may thus experience significant morbidity due to disease progression and treatment toxicity. In order to address some of these problems exercise has been suggested and previously studies have shown improvements of disease specific quality of life and a reduction in treatment-related toxicity. Cohort studies with long term follow up have suggested that physical activity is associated with improved survival in prostate cancer patients. Previously one randomised controlled trial has examined the efficacy of football in prostate cancer patients undergoing androgen deprivation therapy to usual care and reported positive effects on lean body mass and bone markers. Against this background, we wish to examine the effectiveness of community-based football for men diagnosed with prostate cancer. Methods Using a randomised controlled parallel group, multicenter, superiority trial design, two hundred prostate cancer patients will be recruited and randomised (1:1) to either community-based football one hour twice weekly or to a control group. The intervention period will be six months. The primary outcome is quality of life assessed after 12 weeks based on the change from baseline in the Functional Assessment of Cancer Therapy–Prostate questionnaire. Secondary outcomes are change from baseline to six months in quality of life, lean body mass, fat mass, whole body and regional bone markers, as well as physical activity and functional capacity at 12 weeks and six months. Safety outcome variables will be falls resulting in seeking medical assessment and fractures during the six-month period. Discussion Football is viewed as a case for non-professional, supervised community-based team sport for promoting long-term physical activity in men diagnosed with prostate cancer. This randomised trial will provide data on effectiveness and safety for men with prostate cancer when football training is delivered in local football clubs. Trial registration Clinicaltrials.gov identifier:NCT02430792